Multiclass analysis of emerging organic contaminants in tropical marine biota using improved QuEChERS extraction followed by LC MS/MS - Tuan Omar, Tuan Fauzan; Aris, Ahmad Zaharin; Md. Yusoff, Fatimah (Elsevier, 2021)
Marine biota is one of the important components of an ecosystem, and it has been widely used as a pollution indicator for emerging organic contaminants (EOCs) in the coastal zone. Previous studies divulged the concentration of EOCs in various types of biota matrices at trace level detection. EOCs have been associated with several adverse human health effects. Bioaccumulation of EOCs in the food web has been the main concern, and thus a sensitive and selective method for trace quantification of EOCs in biota matrices need to be developed and optimized. Considering various matrix interferences for EOC analysis in marine biota, a combination technique of QuEChERS and solid phase extraction cleanup with detection based on liquid chromatography with tandem mass spectrometry (LC MS/MS) is presented in this study. A method for 16 compounds grouped into four different classes, namely, pharmaceutically active chemicals, phenolic endocrine disrupter compounds, estrogenic hormones, and pesticides, was developed and validated for biota extraction. Satisfactory extraction was obtained for the optimized method with percentage of recovery from 64% to 114% and excellent sensitivity with detection limit in the range of 0.02–3.50 ng/g. Linearity of the standards (in the solvent) in the LC MS-MS analysis ranged from 0.991 to 0.999. The relative standard deviation for intra-day and inter-day repeatability was less than 20%, indicating good-precision analysis. Assessment on the matrix effects showed ionization suppression for all the developed compounds. The developed method was verified by analyzing biota matrices collected from the Klang River estuary. Trace concentrations of EOCs, ranging from 0.05 to 10.76 ng/g, were found in those matrices. Of the 16 targeted compounds, 10 were detected, namely, diclofenac, bisphenol A, sulfamethoxazole, amoxicillin, E2, E1, progesterone, testosterone, primidone, and 4-octylphenol. The other compounds were below the method detection limit.